ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN EFISIENSI PENGELOLAAN ZAKAT DI INDONESIA: STUDI KASUS ORGANISASI PENGELOLA ZAKAT SKALA NASIONAL - Merdeka, Niki Agni Eka Putra; Muid, Dul (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to determine the level of accountability, transparency, and efficiency of OPZs on a national scale in Indonesia. The method used in this research is descriptive analysis. The level of accountability and transparency was analyzed based on the implementation of Internet Financial Reporting (IFR) as measured by a list of disclosure indexes. The level of efficiency was analyzed using the nonparametric Data Envelopment Analysis (DEA) method with production approach and an output-oriented to the assumption of Variable Return to Scale (VRS), with input variables in the form of personnel expenses, operational expenses, and socialization expenses, while the output variables were collection and distribution. The research sample comes from the list of national-scale OPZs in Indonesia in Perdirjenpajak No. PER-15/PJ/2020 selected by purposive sampling method. The data used for the analysis of accountability and transparency comes from the results of observations on the implementation of IFR on the OPZ’s website in September 2021. Meanwhile, the data used for the analysis of efficiency are the OPZ’s financial statements for the 2019-2020 period that have been uploaded on their websites.The results of this study show that the average level of accountability and transparency of 25 OPZ on a national scale in Indonesia until September 2021 is at a low level. This is due to the low awareness of uploading financial reports on the internet, the low quality of financial reports that have been uploaded on the internet, and less than optimal website maintenance and updates.  Meanwhile, the nine OPZ in the efficiency analysis that has efficient zakat management performance is IZI, LMI, BMM, Griya Yatim, Panti Yatim, and NU Care. For inefficient OPZs, namely BAZNAS, Dompet Dhuafa, and Rumah Yatim, they can further improve the quality of governance or provide education and training to staff to be efficient.